Des possiblités développementales pour la mère dans la symbolique post-natale - Hamel, Sylvie; Spain, Armelle (Canadian Journal of Counselling and Psychotherapy, 2011)
This article presents a heuristic study aimed at revealing the meaning of a happened to the main researcher as she was breastfeeding her first child. This phenomenon was the reminiscence of recent and not so recent night dreams. Following self-inquirv, data was gathered from theoretical and empirical literature on psychology of motherhood, identity and symbiosis. Results suggest that, even alter delivery, the mother can remain in a psychological symbiotic relationship with her newborn. Moreover, regression or identity désintégration often seen as characterizing this symbiotic state is reconsidered. The authors present here a less restrictive view of this postnatal experience. Rather than a diagnostic approach, a developmental and a healing perspectives are proposed.